2021
DOI: 10.1007/s00271-020-00713-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a growing maize canopy on solid-set sprinkler irrigation: kinetic energy dissipation and water partitioning

Abstract: The energy of sprinkler irrigation drops splashing on the soil surface or the crop canopy depends on their size and velocity. The kinetic energy of sprinkler irrigation drops is a major factor degrading the soil surface. The effect of a growing maize canopy on sprinkler drop energy dissipation and water partitioning was analyzed. A field experiment was performed on a solid-set sprinkler irrigated plot cropped with maize. Measurements were performed at different locations and heights into the sprinkler layout. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…There is spatial variability in plant canopy structure, and the spatial distribution of the maize canopy structure is such that the greater the distance from the stalk is, the lower the canopy thickness. The results of Nanko et al [38] and Zapata et al [19] on the effects of canopy thickness on the size of throughfall droplets showed that if the plant canopy thickness was relatively large, the diameter of the throughfall droplets would be small. Therefore, when the data collection point was far away from the plant stalk or located in a gap in the canopy, the diameter of throughfall droplets was larger than that at the other location measurement points.…”
Section: Diameter Of Throughfall Dropletsmentioning
confidence: 98%
See 4 more Smart Citations
“…There is spatial variability in plant canopy structure, and the spatial distribution of the maize canopy structure is such that the greater the distance from the stalk is, the lower the canopy thickness. The results of Nanko et al [38] and Zapata et al [19] on the effects of canopy thickness on the size of throughfall droplets showed that if the plant canopy thickness was relatively large, the diameter of the throughfall droplets would be small. Therefore, when the data collection point was far away from the plant stalk or located in a gap in the canopy, the diameter of throughfall droplets was larger than that at the other location measurement points.…”
Section: Diameter Of Throughfall Dropletsmentioning
confidence: 98%
“…The leaf area index and canopy thickness of the plant are substantial canopy structural variables affecting the throughfall DSD. [19,37,38] Nanko et al [37] found that the plant canopy status (i.e., the presence or absence of leaves) was one of the most important factors influencing the throughfall DSD, and that D 50 of throughfall droplets under plants during the leafless stage was significantly greater than that during the leafy stage. Nanko et al [38] and Zapata et al [19] investigated the effects of plant canopy thickness on the DSD and D 50 of throughfall droplets.…”
Section: Throughfall Dsdmentioning
confidence: 99%
See 3 more Smart Citations